2023
DOI: 10.1007/s00392-023-02187-3
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning of patients with congenital heart disease: 45 years after surgery

Abstract: Background Nowadays, more than 90% of patients with congenital heart disease (CHD) reach adulthood. However, long-term impact on neurodevelopment and executive functioning in adults with CHD are not completely understood. Purpose To investigate the self- and informant-reported executive functioning in adults with CHD operated in childhood. Material and methods Longitudinal study of a cohort of patients (n = 194, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“… 12 However, a recent study in a heterogenous sample of adults with CHD showed that self-reported and informant-reported EF scores were similar to normative data and were similar between different CHD types. 42 …”
Section: Discussionmentioning
confidence: 99%
“… 12 However, a recent study in a heterogenous sample of adults with CHD showed that self-reported and informant-reported EF scores were similar to normative data and were similar between different CHD types. 42 …”
Section: Discussionmentioning
confidence: 99%